In situ search for extraterrestrial life: A microbial fuel cell-based sensor for the detection of photosynthetic metabolism - Figueredo, Federico (2015)
Microbial fuel cells (MFCs) are bioelectrochemical systems (BES) capable of harvesting electrons from redox reactions involved in metabolism. In a previous work, we used chemoorganoheterotrophic microorganisms from the three domains of life - Bacteria, Archaea, and Eukarya - to demonstrate that these BES could be applied to the in situ detection of extraterrestrial life. Since metabolism can be considered a common signature of life "as we know it," we extended in this study the ability to use MFCs as sensors for photolithoautotrophic metabolisms. To achieve this goal, two different photosynthetic microorganisms were used: the microalgae Parachlorella kessleri and the cyanobacterium Nostoc sp. MFCs were loaded with nonsterilized samples, sterilized samples, or sterilized culture medium of both microorganisms. Electric potential measurements were recorded for each group in single experiments or in continuum during light-dark cycles, and power and current densities were calculated. Our results indicate that the highest power and current density values were achieved when metabolically active microorganisms were present in the anode of the MFC. Moreover, when continuous measurements were performed during light-dark cycles, it was possible to see a positive response to light. Therefore, these BES could be used not only to detect chemoorganoheterotrophic metabolisms but also photolithoautotrophic metabolisms, in particular those involving oxygenic photosynthesis. Additionally, the positive response to light when using these BES could be employed to distinguish photosynthetic from nonphotosynthetic microorganisms in a sample.